Evaluation of the Anti-tuberculosis and Cytotoxic Potential of the Seaweed Padina australis: Antituberculosis and cytotoxic potential of the seaweed Padina australis - Vaseghi, Golnaz; Zakeri, Narges; Mazloumfard, Fatemeh; Dana, Nasim; Yegdaneh, Afsaneh (Iranian Journal of Pharmaceutical Sciences, 2019)
Marine seaweeds synthesize different types of compounds with various biological activities, including antituberculosis and anticancer effects. The aim of this study was to evaluate anti tuberculosis of Padina australis and cytotoxicity of different fractions of this seaweed. Padinaaustralis was collected from Persian Gulf, identified and extracted by maceration with methanol-ethyl acetate. The extract was evaporated and partitioned by Kupchan method to yield Hexane, dichloromethane, Butanol and water partitions. The anti-tuberculosis activity of the crude extract and cytotoxicity of fractions were investigated using GFPMA and MTT methods. The cell survivals of HeLa cell were decreased by increasing the concentration of extracts. The IC50 value of hexane, dichloromethane, butanol and water partitions were 2.0, 20, 19.7, and 182.7μg/ml, respectively. The crude extract was not active against tuberculosis. This study reveals that different partitions of Padina australis have cytotoxic activity against cancer cell lines.